ECONOMICAL ANALYSIS OF THE CARGO TRANSPORTATION BETWEEN GAZIANTEP&ISTANBUL - Turan, Eda; Celik, Fahri; Dilek, Melike (YILDIZ TECHNICAL UNIV, 2012)
Cargo and passenger transportation services in Turkey is mainly focused on highway transportation and this situation causes uneven distribution. Especially utilization rate for seaway transportation is comparatively low in Turkey which is surrounded by sea on three sides. The highway transportation ratio is not as high as in Turkey and railway, seaway, airway transportation modes as well as pipelines in fluids are also been utilized. In recent years, progress of new transportation systems in the form of integration of these transportation modes in order to offer higher-quality and low cost began to be developed. The intermodal transportation that meets the needs of different distribution and transports all types of cargoes is an important result of this progress. In this study, the feasibility of intermodal cargo transportation system in Turkey is analysed and it is worked to get useful aspect for this system through comparison of the other transportation modes. The most cost-effective transportation mode is investigated for 3000 tonnes of cargoes transportation in Gaziantep & Istanbul line by Levelised Cost Analysis Method and the most effective mode is determined with the comparison of different modes of transportation.
Keywords: Transportation; levelised cost analysis method; intermodal transportation; Engineering